2013
DOI: 10.1002/micr.22206
|View full text |Cite
|
Sign up to set email alerts
|

Identification of perioperative risk factor by laser-doppler spectroscopy after free flap perfusion in the head and neck: A prospective clinical study

Abstract: The aim of this study was to evaluate perioperative flap perfusion using noninvasive monitoring with a laser-Doppler flowmetry and spectrophotometry unit (O2C) and identify whether perioperative blood flow, velocity, hemoglobin level (Hb), and oxygen saturation (SO2 ) measured could be used as indicators of free flap success. Measurements of blood flow, velocity, Hb, and SO2 were performed in 196 microvascular flaps, which had been transferred into the oral cavity to reconstruct ablative defects after surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Possible explanations for this link include an associated greater case complexity, higher blood loss, fluid shifts, depressed wound healing capability, and vessel/tissue desiccation . A recent study by Mücke et al revealed that perioperative blood flow, velocity, hemoglobin level, and oxygen saturation might be critical determinants of flap viability during the immediate 48 hours postoperative period. Although the study authors did not suggest specific values for any of these parameters that would otherwise be indicative of flap failure, there might be considerable utility in trending and addressing these parameters intraoperatively and during the postoperative free flap monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for this link include an associated greater case complexity, higher blood loss, fluid shifts, depressed wound healing capability, and vessel/tissue desiccation . A recent study by Mücke et al revealed that perioperative blood flow, velocity, hemoglobin level, and oxygen saturation might be critical determinants of flap viability during the immediate 48 hours postoperative period. Although the study authors did not suggest specific values for any of these parameters that would otherwise be indicative of flap failure, there might be considerable utility in trending and addressing these parameters intraoperatively and during the postoperative free flap monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…One advantage of this technique is that scintigraphy images can show areas of partial flap hypoperfusion. Several different isotopes have been studied, 147,[198][199][200][201] including 85 Kr, 133 Xe, 22 Na, and 99m Tc. Aygit and Sarikaya 200 demonstrated that this technique was useful in determining flap viability, but note was made of several problems with this technique, making it ultimately unlikely to be useful in monitoring of flaps.…”
Section: Orthogonal Polarized Lightmentioning
confidence: 99%
“…134 This technique was later easily adapted for use in monitoring free flaps. The introduction of fiberoptic fluorometry by Silverman et al 133,134 allowed for the monitoring of elimination as well as perfusion with fluorescein. [135][136][137] Subsequently, other studies showed that using oral fluorescein was possible.…”
Section: Fluorometrymentioning
confidence: 99%
“…In recent years, various new monitoring tools allowing an earlier diagnosis of vascular compromise than conventional bedside monitoring have reportedly improved the flap salvage rates, resulting in improved success rates. New monitoring tools include implantable Doppler systems that allow direct monitoring of vascular anastomotic sites, noninvasive monitoring using near‐infrared spectroscopy, invasive monitoring of metabolic products such as lactic acid levels using microdialysis, and laser Doppler flowmetry …”
Section: Discussionmentioning
confidence: 99%